La Política Exterior de la Unión Europea. Balance del Tratado de Lisboa en materia de Prevención de Conflictos - Martínez Garnelo y Calvo, Giorgiana Karenina (Nómadas. Critical Journal of Social and Juridical Science, 2015)
Study that examines the process that the European Union made in Security Policy matter. After the presentation of The Lisbon Treaty, Europe faces new mechanisms of the regional integration that posed more democracy and greater coherence and institutional visibility. Is in this process in which the Conflict Prevention is one of the most certain bets of the Union, which is reflected in the position of Europe in organizations and nations; this means, a greater cooperation between countries in the European Union. However, the nacional interest of each country is magnified by the crisis and the guidance change on the security and international defense agenda test these new transformations.